2018
DOI: 10.1164/rccm.201706-1161oc
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cells Homeostatically Bind Mitochondrial DNA through TLR9 to Maintain Quiescence and to Prevent Lung Injury

Abstract: RBCs homeostatically bind mtDNA, and RBC-mediated DNA scavenging is essential in mitigating lung injury after CpG-DNA. Our data suggest a role for RBCs in regulating lung inflammation during disease states where cf-mtDNA is elevated, such as sepsis and trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(113 citation statements)
references
References 42 publications
(53 reference statements)
4
107
0
2
Order By: Relevance
“…This damage-associated pattern can activate toll-like receptors leading to a systemic inflammatory response syndrome. [40][41][42] Studies in various patients indeed revealed a higher cell-free mtDNA copy number in patients with clinical outcomes. 22,43,44 Strengths and limitations of the study To our knowledge, this is largest reported study of mtDNA copy numbers in CKD patients using prespecified and centrally adjudicated outcome measures.…”
Section: Oxidative Stress As a Possible Explanation Of The Findingsmentioning
confidence: 98%
“…This damage-associated pattern can activate toll-like receptors leading to a systemic inflammatory response syndrome. [40][41][42] Studies in various patients indeed revealed a higher cell-free mtDNA copy number in patients with clinical outcomes. 22,43,44 Strengths and limitations of the study To our knowledge, this is largest reported study of mtDNA copy numbers in CKD patients using prespecified and centrally adjudicated outcome measures.…”
Section: Oxidative Stress As a Possible Explanation Of The Findingsmentioning
confidence: 98%
“…We quantified mtDNA levels from blood samples drawn at ED presentation and 48 h by using polymerase chain reaction for the mitochondrial ND1 gene, measured in triplicate, as reported previously; log-transformed copy number per microliter was used to ensure normality. 24 Primary and Secondary Outcomes ARDS was defined as previously described applying the Berlin criteria, utilizing data over the first 6 days following presentation. 25 All chest radiographs were assessed by two trained reviewers (J. P. R. and M. G. S. S.).…”
Section: Mtdna Measurementmentioning
confidence: 99%
“…This study does not prove that circulating mtDNA causes ARDS; in fact, lung injury could result in elevated circulating mtDNA at 48 h, although our finding that patients with sepsis and a pulmonary infection source had no mtDNA-ARDS association argues against this reverse causal effect, as does the substantial preclinical evidence from animal models. 7,8,24,36,37 Our ability to identify whether mtDNA is elevated prior to ARDS incidence was limited by the lack of samples available between presentation and 48 h. Further research detailing early plasma mtDNA dynamics during critical illness will help to identify the earliest association and infer a causal relationship between circulating mtDNA and ARDS, a necessary step to inform the potential value of mtDNA pathwayspecific therapies. Nevertheless, this study provides compelling evidence linking mtDNA and ARDS.…”
Section: Messi Cohort: Sepsismentioning
confidence: 99%
“…Dengue virus (DENV) infection induces the release of mtDNA into the cytosol, which upregulates TLR9 expression, binds TLR9 and translocates together with TLR9 into lysosomes to trigger downstream signaling events [26]. Interestingly, in response to the proinflammatory characteristics of mtDNA and to prevent further damage to tissues or organs, such as the lung, red blood cells can bind mtDNA through TLR9 to maintain homeostasis [27]. Another commonly recognized sensor of mtDNA is cyclic GMP-AMP synthase (cGAS), which shares similarities with the antiviral cytosolic double-stranded RNA sensor 2′-5′-oligoadenylate synthase (OAS1) [28].…”
Section: Downregulation Of Mitochondrial Dna (Mtdna)mentioning
confidence: 99%